MATHEMATICAL MODELLING SOLUTIONS FOR STOCK AND COST DEPENDENT INVENTORY IN A LIMITED DISPLAY SPACE WAREHOUSE - Goyal, Shradha; Pandey, Rudresh (International Journal of Supply Chain Management, 2018)
Study in this paper is concerned with optimization of both quantity of order and selling price together, considering EOQ model for items with depreciating nature. It is based on the few assumptions like rate of demand is dependent on level of stock displayed on shelf as well as per unit selling rate, also, the space for stock display is finite. Two mathematical models are studied to investigate the further revised EOQ modelling for obtaining maximum profits and also develop models for such optimized solutions. Justification and analysis of the work developed and studied is done through sensitivity analysis and numerical examples.